Fusarium species and mycotoxin contamination in maize in Buenos Aires province, Argentina - Castañares, Eliana; Martínez, Mauro; Cristos, Diego Sebastian; Rojas, Dante Emanuel; Lara, Bruno; Stenglein, Sebastian Alberto; Dinolfo, María Inés (Springer, 2019)
Maize is one of the most important crops in Argentina. This crop can be affected by the presence of different Fusarium species, causing two distinct diseases known as Fusarium ear rot and Gibberella ear rot. In this study, a total of 90 samples from commercial fields of Buenos Aires province in Argentina were collected during the 2015, 2016 and 2017 harvest seasons with the aim to evaluate Fusarium species presence, mycotoxin content and to establish a relationship between the main Fusarium mycotoxins infecting maize grains and the environmental conditions. The results showed that F. verticillioides was the most isolated species followed by F. subglutinans, species of Fusarium graminearum species complex, F. proliferatum, and F. cerealis varying their presence according to the harvest season evaluated. Regarding mycotoxins, deoxynivalenol and 3-acetyl-deoxynivalenol showed content from 281.26 ± 22.51 to 359.02 ± 42.57 μg/kg in the 3 yrs evaluated, while 15-acetyl-deoxynivalenol, nivalenol, and zearalenone were not found. With regard to B1 and B2 fumonisins, these mycotoxins were detected below the detection limit of 0.3 μg/kg in some maize samples in the 3 yrs. The selection of maize genotypes, cultural practices, and climatic conditions could be responsible for the Fusarium species found and their respective mycotoxin production. Due to worldwide concern about food security and the potential risk the global climate change could impart, it will be necessary to develop predictive models based on meteorological conditions to determine the risk of Fusarium presence and mycotoxin production in maize similar to those developed in other crops.